Processos de formulação e acompanhamento de planos à luz da estratégia como prática: os casos das gestões da UFSCar de 1992 a 2008 - Zabotto, Marco Antonio Cavasin (2014)
Strategy as Practice (SaP) is a recent theory that appeared at the end of the last century as an approach which assumes the strategy as something that organizations do and not as something that they possess. Based on this premise, its focus is on micro activities carried out by the strategists of different organization s hierarchical levels, called practitioners. They apply theoretical and practical models, called practices, to carry out the strategic praxis. This research was performed based on this approach and seeks to analyze the strategic planning processes adopted by a Federal University in Brazil, considering four consecutive administrations. The main objectives are: to propose a model for the development and monitoring of strategic plans at the Federal Institutions of Higher Education or other public education institutions in Brazil; and to propose a procedure that could facilitate the analysis of their plans. The lack of empirical studies based on the SaP approach or on its applications in studies of planning processes in public universities has been highlighted during the bibliographical research performed in national and international qualified databases, covering publications in journals, books, thesis and dissertations. It was found that the lack of references when one wants to get applications of SaP in universities is even greater. The development of this research took place at the Federal University of São Carlos, based on descriptive case studies of four successive administration cycles each one corresponding to four years. Semi-structured interviews were conducted with the rector and professors who were responsible for coordinating important projects during each administration term. An exam of several documents for each administration cycle was also performed and enabled to collect data and to analyze the processes of formulating and monitoring strategic plans. Each management term was described and analyzed considering five elements: the context (the internal and the external environment) of the institution, the planning (formulation) process, the monitoring process of the plan, the results achieved by management, and the role and activities of the university leader, the rector. The analysis of strategizing processes was carried out based on SaP s constructs: practices, praxis and practitioners. The information obtained in accordance with SaP s constructs was valuable to describe, to comprehend and to compare the planning and monitoring processes implemented in each of the four administration cycles. The study also demonstrates consistent with the literature the importance of rectors roles in formulation and monitoring processes. The main results obtained by the analysis of the four administration cycles supported the proposition of a strategic planning model for Federal Universities and of a series of guidelines and steps to facilitate the analysis of strategic plans, considering the SaP s precepts, in these universities and other related institutions.